Social inequities and clinical outcomes in young women with cervical cancer: Real-world evidence - Luiza Cupertino Bérgomi; Giselle de Souza Carvalho; Lucas Zanetti de Albuquerque; Daniel Gonçalves Kischinhevsky; Alexssandra Lima Siqueira dos Santos; Luiza de Freitas Maciel; Isabele Ávila Small; Jessé Lopes da Silva; Andreia C. de Melo (PLoS ONE, 2026)
Objective To assess the influence of social inequities and clinicopathological factors on survival outcomes in young women with cervical cancer treated at a comprehensive public cancer center in Brazil. Methods This retrospective analysis reviewed the medical records of women aged 18–39 diagnosed with cervical cancer at the Brazilian National Cancer Institute between January 2017 and December 2021, assessing demographic characteristics and survival outcomes. Results This analysis included 475 patients with a mean age of 33.6 years, with the majority being non-white (67.7%), never married women (68.0%), and having a low education level (< 8 years) (86.1%). Multivariate analysis indicated that a lower education level was associated with advanced stage (p = 0.001). Recurrence or progression occurred in 224 patients (47.2%), mainly as distant metastases (56.7%). The median progression-free survival (PFS) was 19.8 months, with two-year rates of 81.6%, 45.7%, 28.2%, and 6.2% for stages I, II, III, and IV, respectively. Shorter PFS was correlated with lower education level (p = 0.009), alcohol consumption (p = 0.026), undifferentiated carcinoma (p = 0.007), and advanced disease stage (p < 0.001). The median overall survival (OS) was 35.1 months, with five-year rates of 82.9%, 42.7%, 23.7%, and 9.7% for stages I, II, III, and IV, respectively. Factors associated with shorter OS included lower education level (p = 0.005), undifferentiated carcinoma (p = 0.006), and advanced stage (p < 0.001). Conclusion Undifferentiated carcinomas and advanced stages negatively influence the prognosis of young women with cervical cancer. Social factors may also be correlated with poorer outcomes, especially alcohol consumption and lower education levels.